Human being properties of saplings growing up algorithm - Karci, Ali (Ieee, 2007)
The human culture and cognition are consequence of the thinking capability of human, and thinking is a social activity. People have similar idea and opinion interacts, and interactions force people to have similar idea and interaction take place locally. However, its effect is global. In this study, we try to determine / define the computational thinking for Saplings Growing up Algorithm (SGuA) which belongs to evolutionary algorithms. Thinking capability can be defined based on the process interaction for similar solutions. SGuA has four operators: mating, branching, vaccinating and surviving. We determined the computational thinking capability for each operator. Finally, we determined computational thinking capability of SGuA.
5th IEEE International Conference on Computational Cybernetics -- OCT 19-21, 2007 -- Gammarth, TUNISIA